(untitled) (Research, Society and Development, 2022)
Objective: to estimate the prevalence of musculoskeletal disorders symptoms in mineral extraction workers. Method: A quantitative, descriptive, and cross-sectional study was conducted in the village of Pirinã, Municipality of Pinheiro, Maranhão State. The research universe comprised the workers of stone extraction. The sample was of convenience for the inclusion of individuals who presented painful symptoms in some anatomical region of the body. Data collection was done through the use of two instruments, the Individual Questionnaire (IQ) and the Nordic Musculoskeletal Symptoms Questionnaire (NSQ). Results: The majority presented pain in the lumbar spine, dorsal column, hands/wrists, and shoulders, requiring time off work. In relation to physical tiredness during the workday, 80% reported tiredness at the end of the workday. It was also observed that 23 workers had worked for more than 10 years and worked 3-4 hours a day during the week. Final considerations: The results draw attention to the recurrence of pain among rural workers, which can interfere with their quality of life, cause irreversible and/or chronic sequels, and decrease their productivity. The ergonomic analysis in this context can act preventing the incidence of accidents and avoiding disabilities.